Effects of Processing Triticum spp on Total Aflatoxins and Its Distribution into Wheat Products - , J. R. Wartu; , C. M. Z. Whong; , I. O. Abdullahi; , J. B. Ameh (Archives of Current Research International, 2017)
Aflatoxins are carcinogenic. The presence of such mycotoxin in food and feed could pose health threat to both human and animals. Aims: The aim of this research were to study the distribution and the fate of total aflatoxins from in-process aflatoxin contaminated wheat into products. Place and Duration of Study: The study was carried out in a low tonnage 100 kg/h processing unit from northern Nigeria from February - November, 2016. Methodology: Standard methods were adopted to determine some proximate compositions of wheat and roller mill processed wheat products (wheat flour, semolina, brown flour and bran). ELISA was employed to detect and quantify total aflatoxin from the samples. Results: Tempered wheat presented higher moisture content (15.5%) followed by wheat flour (14.8%) and least in bran (12.42%). Highest ash values was recorded in bran (1.55 dm%), followed by raw wheat (1.31 dm%), damped wheat (1.18 dm%), brown flour (0.84 dm%), wheat flour (0.64 dm%) and least in semolina (0.50 dm%). Mean percentage protein content decreased gradually from the raw material (15.18%) to wheat flour (12.34%). This represents 18.71% reduction in protein content during processing at 70% extraction. The effects of wheat flour extraction rate and total aflatoxin retention presented positive correlation. As the extraction rate increased, the aflatoxin retention also increased with increasing ash content. At 60% extraction, aflatoxin retention was 2.0% indicating decontamination of 98.0% total aflatoxins with corresponding 0.57%dm ash content. Increasing the extraction rate from 60 – 75%, the ash content and the total aflatoxin retention increased from 0.57 - 0.82%dm and 2.0 - 56.59% respectively while total aflatoxin decontamination decreased from 98.0 – 43.41%. Conclusion: This research has demonstrated that aflatoxin contaminated wheat used for processing could redistribute aflatoxins into wheat products thus the need for strict surveillance of raw material by processors and regulatory bodies during importation and at factory level to safeguard incidence of aflatoxicosis in consumers.